1993
DOI: 10.1149/1.2056195
|View full text |Cite
|
Sign up to set email alerts
|

AC Conductivities of Neopentylglycol and 2‐Amino‐2‐Methyl‐1,3‐Propanediol

Abstract: Neopentylglycol (NPG) and 2-amino-2-methyl-l,3-propanediol (AMPL) are potential thermal energy storage materials which undergo energetic solid-state phase transformations. Both NPG and AMPL have monoclinic low temperature a-phase and cubic high temperature ~-phase structures. These polymorphic changes in structure occur at 41 and 80~ for NPG and AMPL, respectively. Below the a --> ~/transition, these compounds are dielectric materials with conductivities on the order of 10 -8 S/m (at 22~ and 10 -9 S/m (at 25~ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Crystallographic and thermodynamic parameters of the pure polyalcohol and amines are already established in the literature [5][6][7][8][9][10][11][12][13]. The low temperature crystal structure of AMPL is reported by Rose et al [5] as monoclinic with lattice parameters: a=8.62 Å, b=11.00 Å, c=6.10 Å, =93.32, V=580.3 Å 3 at 293K (Z=4).…”
Section: Introductionmentioning
confidence: 96%
“…Crystallographic and thermodynamic parameters of the pure polyalcohol and amines are already established in the literature [5][6][7][8][9][10][11][12][13]. The low temperature crystal structure of AMPL is reported by Rose et al [5] as monoclinic with lattice parameters: a=8.62 Å, b=11.00 Å, c=6.10 Å, =93.32, V=580.3 Å 3 at 293K (Z=4).…”
Section: Introductionmentioning
confidence: 96%
“…Rose et al [16] reported the low temperature phase structure of AMPL to be monoclinic with lattice parameters; a ¼8.62 Å, b¼ 11.00 Å, c ¼6.10 Å, β¼93.32°, V¼580.3 Å 3 at 293 K (Z¼ 4). Chandra et al [17,18] reported high temperature phase structure of AMPL as BCC with a ¼6.7 Å above 357 K at which the hydrogen/nitrogen bond configuration changes and an isotropic but orientationally disordered BCC structure forms. It should be noted that polyalcohols, such as, pentaerythritol (C 5 H 12 O 4 ) [11], pentaglycerine (C 5 H 12 O 3 ) and others with tetrahedral C-C configuration and O-H…O bonds have FCC (γ or γ') high temperature structure whereas the amine compounds with O-H…N and O-H…O bonds, such as AMPL or TRIS have BCC obtained unlike most of the other plastic crystals which have FCC structure [5].…”
Section: Introductionmentioning
confidence: 99%
“…There is a disconti- where r = 2 ~v. Following the treatments of Jonscher and Almond ~8' 29 for hopping conductivity in ionic conductors, the ac conductivity may be described in the absence of low frequency dispersion as n l-n ~(o~) = K% + Ko~ % [9] where % is defined as the ion hopping rate or the frequency of the peak in the dielectric loss, and K is a constant of proportionality related to the concentration of mobile ions, the hopping distance, and density of sites per unit volume. Factoring out K% from this expression and assuming the dc conductivity ~(0) = Kr (d n…”
Section: Dielectric Relaxation Times and Frequency Response--mentioning
confidence: 99%